KEBIJAKAN PENINGKATAN PEMANFAATAN LAYANAN PERPUSTAKAAN DAERAH DALAM MENDUKUNG PENGUATAN LITERASI SISWA SEKOLAH DASAR DI KABUPATEN PURBALINGGA - Haryanti (JISPE Journal of Islamic Primary Education, 2026)
The low utilization of regional library services has become a major challenge in strengthening literacy among elementary school students in Purbalingga Regency. This study aims to analyze the current utilization of regional library services, identify the main problems and their root causes, and formulate the most appropriate policy strategy to improve library utilization. A qualitative case study approach was employed. Data were collected through semi-structured interviews, observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that library utilization remains suboptimal, as reflected by low visitor numbers, limited active membership, and weak public participation in literacy programs. Three major issues were identified: students tend to obtain information from sources outside the library, library-based literacy programs have not effectively engaged students, and libraries have not fully functioned as lifelong learning centers. The root cause lies in the mismatch between existing library information services and students' information-seeking behavior. Based on Bardach's feasibility criteria, the User-Centered Library Services policy emerged as the most feasible alternative due to its strong technical, economic, social, and political feasibility. The policy is expected to enhance library utilization and strengthen the contribution of regional libraries to elementary school literacy development.